1986
DOI: 10.1177/088610998600100105
|View full text |Cite
|
Sign up to set email alerts
|

A Feminist Approach to Social Work Research

Abstract: A central contributor to the current dissatisfaction with social work research, the author argues, is that most of the research produced for the profession uses a male model of knowledge development that is alien to women, who constitute the majority of those whose task it is to put the knowledge into action. This article analyzes female and male methodologies in terms of their respective themes of connection and separation and explores the ways in which female methodologies can be incorporated into social wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…Through observational research, it sought to understand how the organizational structure of a shelter whose rhetoric was one of empowerment actually affected the different members. METHODOLOGY This qualitative, participant-observation study was influenced by recent discussions of feminist research methodology (see, for example, Davis, 1986;Dobash & Dobash, 1981;Kelly, 1988). Feminist researchers have a particular relationship to their work.…”
mentioning
confidence: 99%
“…Through observational research, it sought to understand how the organizational structure of a shelter whose rhetoric was one of empowerment actually affected the different members. METHODOLOGY This qualitative, participant-observation study was influenced by recent discussions of feminist research methodology (see, for example, Davis, 1986;Dobash & Dobash, 1981;Kelly, 1988). Feminist researchers have a particular relationship to their work.…”
mentioning
confidence: 99%
“…While some feminists like Davis (1986) suggested that qualitative methods were most compatible with feminist research for giving voice to the voiceless, others, exemplified by Harding in the social sciences (1991,2006), do not think feminist research is defined by its methodology. Swigonski's (1993) discussion of standpoint theory incorporates the idea of critical consciousness: an achieved understanding of how gender (in this case) shape's both one's experiences and one's knowledge of the world, often distorting knowledge when gender is not considered and enriching it when the subjugated knowledge of marginalized women is taken into account.…”
Section: Feminist and Post-colonial Analysesmentioning
confidence: 99%
“…Abramovitz (1987), Burden and Gottlieb (1987), Kravits (1982), and the Hunter College's Project on Curriculum Integration (1987) provide reviews of the new scholarship on women for inclusion in the practice, policy, and human behavior in the social environment sequences. Roseman and Ruckdeschel (1981) and Davis (1986) look at how to integrate gender content into the research sequence, and Berkun (1984) focuses on the field component. Hooyman, Leighninger and Summers (1988) have collected a variety of syllabi from social work courses addressing gender issues across the range of curriculum sequences.…”
Section: Recommendations and Blueprints For Changementioning
confidence: 99%